2020
DOI: 10.3389/fbioe.2020.00100
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanoparticles: Shedding Light on Immunotoxicity and Hemocompatibility

Abstract: Nanoparticles (NPs) assumed an important role in the area of drug delivery. Despite the number of studies including NPs are growing over the last years, their side effects on the immune system are often ignored or omitted. One of the most studied polymers in the nano based drug delivery system field is chitosan (Chit). In the scientific literature, although the physicochemical properties [molecular weight (MW) or deacetylation degree (DDA)] of the chitosan, endotoxin contamination and appropriate testing contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 65 publications
12
54
0
1
Order By: Relevance
“…The percent of hemolysis from all nanoparticles was below 2%, indicating the hemocompatibility of nanoparticles. Nanostructured systems are considered non-toxic if the hemolysis value is below 5%, according to the ASTME2524-08 standard [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The percent of hemolysis from all nanoparticles was below 2%, indicating the hemocompatibility of nanoparticles. Nanostructured systems are considered non-toxic if the hemolysis value is below 5%, according to the ASTME2524-08 standard [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, some CH formulations have the ability to induce NO production as part of the oxidative stress response, 59 while others have no effect. 80 It was also reported that CH possesses the ability to reduce the LPS-induced NO levels by Raw 264.7 macrophages. 80,82 This conflicting data can be explained by the preparation procedures of the CH samples and their physicochemical characteristics, such as composition, size, charge and surface reactivity.…”
Section: Discussionmentioning
confidence: 96%
“…80 It was also reported that CH possesses the ability to reduce the LPS-induced NO levels by Raw 264.7 macrophages. 80,82 This conflicting data can be explained by the preparation procedures of the CH samples and their physicochemical characteristics, such as composition, size, charge and surface reactivity. 76 Taking into consideration the general results from all assays, and the fact that DPBS outcomes are comparable to those of non-treated cells, we concluded that this particle suspension medium did not influence the data.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The optimized mild and self-controlled system allowed the encapsulation of hPAH in CS nanoparticles, maintaining the enzyme’s functional and biophysical properties. However, CS has been reported as potentially immunogenic and it has also been generally described as a haemostatic material that by a complex series of events, such as protein adsorption, platelet and leukocyte adhesion and activation of coagulation pathway, may potentially result in thrombogenicity [ 12 ]. In line with these observations, depending on its DD, molecular mass (MM) and protonation, CS has been applied as an adjuvant in the development of vaccines and as a haemostatic and complement activating material.…”
Section: Introductionmentioning
confidence: 99%